Variations in the medical treatment of inflammatory bowel disease among gastroenterologists - Singh, Shailendra (Gastroenterol Rep (Oxf), 2018)
BACKGROUND AND AIMS: With expanding available treatment options and evolving understanding of the risks and benefits of medical therapies for inflammatory bowel disease (IBD), there is the possibility of significant variations in treatment and outcomes. Little is known about the variation in treatment between IBD specialists and other gastroenterology (GI) physicians. Evaluating possible variations is an important first step to help address standardized care and optimize treatment. We studied the differences in use of biologics and immunomodulators in the management of IBD patients at a tertiary care hospital between IBD-trained physicians and other gastroenterologists. METHODS: A total of 325 IBD patients were included in the analysis. Of these, 216 patients received care with an IBD physician and 109 had other GI/non-IBD physicians as their main caregivers. RESULTS: The unadjusted use of immunomodulators (35.6% vs 16.5%, p = 0.001), biologics (45.8% vs 22.9%, p =0.001) and dual therapy (biologics and immunomodulator) (14.4% vs 3.7%, p =0.001) was significantly higher in the IBD-physician group. These differences in therapy between the two groups remained after adjusting for patient and disease characteristics. CONCLUSION: There are significant variations in the treatment of patients with IBD by GI physicians. The use of biologics and immunomodulators is higher in GI physicians with dedicated IBD interest and training.